Panduan Praktikum Fisika Dasar 1 Berbasis Guided Inquiry Terhadap Peningkatan Hard Skills dan Soft Skills Mahasiswa - Suprianto Suprianto; S. Ida Kholida; Herman Jufri Andi (Momentum: Physics Education Journal, 2017)
Abstract This study aims to analyze the significant influence of the use of first basic physics guide based on a guided inquiry to increased hard skills and soft skills of students. The experimental design used was "One Group Pretest-Postest Control Groups Design". This research was conducted at Integrated Laboratory of Islamic University of Madura. The sample of the study is the students who follow the first Basic Physics Practicum. The instruments used are hard skills observation sheet and student soft skills. Data analysis using SPSS16 for windows software help. Based on the research results, the average value of hard skills posttest is 4.01 with the category "Good", while the average value of soft skills is 4.35 which is categorized as "Excellent". For analysis using SPSS16 for windows obtained t-test hard skills and soft skills of student equal to 13,175 and 12,551 with sig. 0.00. This indicates that there are significant differences in students' hard skills and soft skills during pretest and posttest. From the result of the research, it can be concluded that there is a significant influence of the use of first basic physics guide based on a guided inquiry to increased of hard skills and soft skill of students. Abstrak Penelitian ini bertujuan untuk menganalisis adanya pengaruh yang signifikan penggunaan panduan praktikum fisika dasar 1 berbasis guided inquiry terhadap peningkatan hard skills dan soft skill mahasiswa. Rancangan eksperimen yang digunakan adalah " One Group Pretest-Postest Control Groups Design". Penelitian ini dilakukan di Laboratorium Terpadu Universitas Islam Madura. Sampel penelitian adalah mahasiswa yang mengikuti matakuliah Praktikum Fisika Dasar 1. Instrumen yang digunakan adalah lembar pengamatan hard skills dan soft skills mahasiswa saat praktikum fisika dasar 1. Analisis data menggunakan bantuan software SPSS16 for windows. Berdasarkan hasil penelitian diperoleh nilai rerata posttest hard skills sebesar 4,01 dengan kategori Ã¢â‚¬Å“BaikÃ¢â‚¬Â, sedangkan nilai rerata soft skills sebesar 4,35 yang berkategori Ã¢â‚¬Å“Sangat BaikÃ¢â‚¬Â. Untuk uji analisis menggunakan SPSS16 for windows diperoleh t hitung hard skills dan soft skills mahasiswa sebesar 13,175 dan 12,551 dengan sig. 0.00. Hal ini menunjukkan bahwa ada perbedaan yang signifikan hard skills dan soft skills mahasiswa saat pretest dan posttest. Dari hasil penelitian dapat disimpulkan bahwa ada pengaruh yang signifikan penggunaan panduan praktikum fisika dasar 1 berbasis guided inquiry terhadap peningkatan hard skills dan soft skill mahasiswa.